Intraoperative Hemodynamic and Echocardiographic Measurements Associated With Severe Right Ventricular Failure After Left Ventricular Assist Device Implantation. (January 2019) - Gudejko, Michael D.; Gebhardt, Brian R.; Zahedi, Farhad; Jain, Ankit; Breeze, Janis L.; Lawrence, Matthew R.; Shernan, Stanton K.; Kapur, Navin K.; Kiernan, Michael S.; Couper, Greg; Cobey, Frederick C.
Abstract : BACKGROUND: Severe right ventricular failure (RVF) after left ventricular assist device (LVAD) implantation increases morbidity and mortality. We investigated the association between intraoperative right heart hemodynamic data, echocardiographic parameters, and severe versus nonsevere RVF. METHODS: A review of LVAD patients between March 2013 and March 2016 was performed. Severe RVF was defined by the need for a right ventricular mechanical support device, inotropic, and/or inhaled pulmonary vasodilator requirements for >14 days. From a chart review, the right ventricular failure risk score was calculated and right heart hemodynamic data were collected. Pulmonary artery pulsatility index (PAPi) [(pulmonary artery systolic pressure − pulmonary artery diastolic pressure)/central venous pressure (CVP)] was calculated for 2 periods: (1) 30 minutes before cardiopulmonary bypass (CPB) and (2) after chest closure. Echocardiographic data were recorded pre-CPB and post-CPB by a blinded reviewer. Univariate logistic regression models were used to examine the performance of hemodynamic and echocardiographic metrics. RESULTS: A total of 110 LVAD patients were identified. Twenty-five did not meet criteria for RVF. Of the remaining 85 patients, 28 (33%) met criteria for severe RVF. Hemodynamic factors associated with severe RVF included: higher CVP values after chest closure (18 ± 9 vs 13 ± 5 mm Hg; P = .0008) in addition to lower PAPi pre-CPB (1.2 ± 0.6 vs 1.7 ± 1.0; P = .04) and after chest closure (0.9 ± 0.5 vs 1.5 ± 0.8; P = .0008). Post-CPB echocardiographic findings associated with severe RVF included: larger right atrial diameter major axis (5.4 ± 0.9 vs 4.9 ± 1.0 cm; P = .03), larger right ventricle end-systolic area (22.6 ± 8.4 vs 18.5 ± 7.9 cm 2 ; P = .03), lower fractional area of change (20.2 ± 10.8 vs 25.9 ± 12.6; P = .04), and lower tricuspid annular plane systolic excursion (0.9 ± 0.2 vs 1.1 ± 0.3 cm; P = .008). Right ventricular failure risk score was not a significant predictor of severe RVF. Post-chest closure CVP and post-chest closure PAPi discriminated severe from nonsevere RVF better than other variables measured, each with an area under the curve of 0.75 (95% CI, 0.64–0.86). CONCLUSIONS: Post-chest closure values of CVP and PAPi were significantly associated with severe RVF. Echocardiographic assessment of RV function post-CPB was weakly associated with severe RVF.